Orally Administered Liposomal Lactoferrin Inhibits Inflammation‐Related Bone Breakdown Without Interrupting Orthodontic Tooth Movement. Issue 10 (1st October 2013) - Kawazoe, A.; Inubushi, T.; Miyauchi, M.; Ishikado, A.; Tanaka, E.; Tanne, K.; Takata, T.
Abstract : Background: Bovine lactoferrin (bLF) modulates the production of tumor necrosis factor‐alpha (TNF‐α) and inhibits alveolar bone breakdown associated with periodontitis. This study is designed to examine the effects of orally administered liposomal bLF (LbLF) on orthodontic force (OF)‐induced alveolar bone remodeling during experimental tooth movement. Methods: Two groups of male Wistar rats were treated with either LbLF or control solution in drinking water 7 days before OF application. Lipopolysaccharide (LPS) was injected into the gingival sulcus in half the rats in each group. Thus, four groups: OF, OF+LbLF, OF+LPS, and OF+LPS+LbLF were established. Results: Orally administered LbLF significantly reduced apical migration of junctional epithelium in the OF and OF+LPS groups. In OF+LPS, osteoclast number in the alveolar crestal area was increased by LPS treatment, whereas osteoclast number was significantly reduced in OF+LPS+LbLF through suppression of TNF‐α production. Osteoclastic induction in the middle part, mainly from OF application, was not affected by LbLF administration. Inhibition of tooth movement was not induced by LbLF. Conclusions: Orally administered LbLF significantly inhibits LPS‐induced alveolar bone resorption but not OF‐induced bone remodeling. LbLF could be a potent therapeutic and preventive agent to control periodontal inflammation in patients undergoing orthodontic treatment.